Family-Based Interventions for the Prevention of Substance Abuse and Other Impulse Control Disorders in Girls. (3rd March 2014) - Kumpfer, K. L.
Abstract : Standardized family-based interventions are the most effective way of preventing or treating adolescent substance abuse and delinquency. This paper first reviews the incidence of adolescent substance abuse worldwide emphasizing gender and causes by etiological risk and protective factors. New epigenetic research is included suggesting that nurturing parenting significantly prevents the phenotypic expression of inherited genetic diseases including substance abuse. Evidence-based family interventions are reviewed including family change theories behind their success, principles and types of family-based interventions, research results, cultural adaptation steps for ethnic and international translation, and dissemination issues. The author's Strengthening Family Program is used as an example of how these principles of effective prevention and cultural adaptation can result in highly effective prevention programs not only for substance abuse, but for other impulse control disorders as well. The conclusions include recommendations for more use of computer technologies to cut the high cost of family interventions relative to youth-only prevention programs and increase the public health impact of evidence-based prevention programs. The paper recommends that to reduce health care costs these family-based approaches should be applied to the prevention and treatment of other impulse control disorders such as obesity and type 2 diabetes, sexually transmitted diseases, and delinquency.